2016
DOI: 10.5465/amj.2014.0601
|View full text |Cite
|
Sign up to set email alerts
|

Different Views of Hierarchy and Why They Matter: Hierarchy as Inequality or as Cascading Influence

Abstract: Hierarchy is a reality of group life, for humans and for most other group-living species. However, there remains considerable debate about whether and when hierarchy can promote group performance and member satisfaction. We suggest that progress in this debate has been hampered by a lack of clarity about hierarchy and how to conceptualize it. Whereas prevailing conceptualizations of hierarchy in the group and organization literature have focused on inequality in member power or status (i.e., centralization or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
206
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 146 publications
(227 citation statements)
references
References 96 publications
15
206
1
Order By: Relevance
“…Despite the near ubiquity of informal group hierarchies, research has shown that the strength of informal hierarchical differentiation varies widely, with some groups exhibiting more pronounced and clear‐cut influence differences between their members than others (Bunderson, Van der Vegt, Cantimur, & Rink, ; Schmid Mast, ). This raises important questions about the antecedent conditions that may shape a group's informal hierarchy strength.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the near ubiquity of informal group hierarchies, research has shown that the strength of informal hierarchical differentiation varies widely, with some groups exhibiting more pronounced and clear‐cut influence differences between their members than others (Bunderson, Van der Vegt, Cantimur, & Rink, ; Schmid Mast, ). This raises important questions about the antecedent conditions that may shape a group's informal hierarchy strength.…”
Section: Introductionmentioning
confidence: 99%
“…As such, this research has not investigated how groups develop distinct patterns of informal hierarchical strength, denoting how a group, as a whole, is characterized by its members' dyadic influence and deference relations (cf. Bunderson et al, ; Krackhardt, ; Oedzes, Rink, Walter, & van der Vegt, ). For example, even if informal leadership roles are shared between individual members, a group may exhibit either a relatively weak (if most members' dyadic influence relations are reciprocal) or a relatively strong informal hierarchy (if most members' dyadic influence relations are unidirectional; Bunderson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations